Perioperative Antibiotic Choice in Labored versus Unlabored Cesareans and Risk of Postcesarean Infectious Morbidity - Hopkins, Maeve K.; Dotters-Katz, Sarah; Boggess, Kim; Heine, R. Phillips; Smid, Marcela (American Journal of Perinatology, 2018)
Objective This study aims to estimate postcesarean infectious morbidity in women receiving perioperative β-lactam versus non-β-lactam antibiotics.Methods We conducted a retrospective cohort analysis of the Maternal-Fetal Medicine Unit Cesarean Registry. The exposure was β-lactam perioperative antibiotics versus non-β-lactam regimens at cesarean delivery (CD). We stratified by labored versus unlabored CD. The primary composite outcome included wound infection, seroma, hematoma, endometritis, readmission due to wound complication, or debridement. Multivariable logistic regression estimated odds of wound complication by antibiotic regimen after adjusting for relevant confounders.Results Our analysis included 43,735 women who delivered via CD, 48% following labor. In both groups, 95% of women received β-lactam antibiotics. In the labored CD group (n = 20,860), there was no significant difference in primary outcome by β-lactam versus non-β-lactam antibiotics (10.5 vs. 9.9%, p = 0.53). In the unlabored CD group (n = 22,875), women receiving non-β-lactam antibiotics were more likely to experience a wound complication compared with those in the β-lactam group (6.2 vs. 4.7%, p = 0.02, adjusted odds ratio: 1.39, 95% confidence interval: 1.08–1.80) after adjustment for clinical confounders.Conclusion In unlabored CD, non-β-lactam antibiotics have a higher risk of wound complications compared with β-lactam regimens. Further study to optimize antibiotic prophylaxis for β-lactam allergic women undergoing unlabored CD is warranted.
Keywords: cesarean delivery; infectious morbidity; non-β-lactam antibiotics; penicillin allergy